2015
DOI: 10.1111/bjh.13622
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil therapy for severe immune thrombocytopenia

Abstract: *We regret to note that Dr Roberto Stasi, one of our co-authors, has very sadly passed away since the time of original data collection. We would like to acknowledge his valuable contribution to this work SummarySevere immune thrombocytopenia purpura (ITP) presents a clinical challenge. Second-line treatment options are variable without a precise protocol. We present 46 severe ITP patients treated with mycophenolate mofetil (MMF), retrospectively identified from three London teaching hospitals. Data was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 20 publications
3
32
0
1
Order By: Relevance
“…This favourable outcome is in agreement with the results from a recently published series of 46 adults treated with MMF for ITP (Taylor et al, 2015). This favourable outcome is in agreement with the results from a recently published series of 46 adults treated with MMF for ITP (Taylor et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This favourable outcome is in agreement with the results from a recently published series of 46 adults treated with MMF for ITP (Taylor et al, 2015). This favourable outcome is in agreement with the results from a recently published series of 46 adults treated with MMF for ITP (Taylor et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings contrast with several reports or clinical studies showing prolonged response with such therapies, but patients showed less refractory disease than our patients. [13][14][15][16][17][18][19] Despite the efficacy of HSCT, the high risk of mortality associated with this procedure (1 death in our cohort) argues for its proposal for patients with no alternative therapeutic option only. However, the combination of Tpo-RAs with immunosuppressant drugs was effective with an overall response rate (R 1 CR) of 70% in the 10 patients who received this treatment.…”
Section: Discussionmentioning
confidence: 82%
“…[76][77][78][79][80][81][82] We begin MMF at a dose of 500 mg orally twice per day and increase the dose to 1000 to 1500 mg twice per day after 2 weeks. Protocols that use this approach have demonstrated overall response rates of 50% to 60%.…”
Section: Tiermentioning
confidence: 99%
“…Protocols that use this approach have demonstrated overall response rates of 50% to 60%. [76][77][78][79][80][81] Durability of response after discontinuation of therapy is variable. 77,79,82 MMF is generally well tolerated; principal adverse effects include headache and gastrointestinal symptoms.…”
Section: Tiermentioning
confidence: 99%